2019
DOI: 10.1111/nph.15743
|View full text |Cite
|
Sign up to set email alerts
|

Pollination effectiveness in a generalist plant: adding the genetic component

Abstract: Summary The pollination effectiveness of a flower visitor has traditionally been measured as the product of a quantity component that depends on the frequency of interaction and a quality component that measures the per‐visit effects on plant reproduction. We propose that this could be complemented with a genetic component informing about each pollinator's contribution to the genetic diversity and composition of the plant progeny. We measured the quantity and quality components of effectiveness of most polli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 102 publications
(135 reference statements)
0
32
0
1
Order By: Relevance
“…Although H. tortuosa is visited by multiple species of hummingbirds, our study suggests that this pollination network has high cryptic specialization (Fenster et al, 2004), where successful pollination largely comes from the few traplining hummingbird species. A reduction in the number of realized pollinators has been reported in other species of plants that are visited by multiple functional groups of pollinators (Watts et al, 2012; Rhodes et al, 2017; Valverde et al, 2019; Temeles et al, 2019). Therefore, our results support a growing body of work showing that the total number of floral visitors is neither a good predictor nor any guarantee of effective pollen transfer, especially in the Anthropocene where habitat loss and fragmentation are expected to continue (Defries et al, 2010; Hansen et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although H. tortuosa is visited by multiple species of hummingbirds, our study suggests that this pollination network has high cryptic specialization (Fenster et al, 2004), where successful pollination largely comes from the few traplining hummingbird species. A reduction in the number of realized pollinators has been reported in other species of plants that are visited by multiple functional groups of pollinators (Watts et al, 2012; Rhodes et al, 2017; Valverde et al, 2019; Temeles et al, 2019). Therefore, our results support a growing body of work showing that the total number of floral visitors is neither a good predictor nor any guarantee of effective pollen transfer, especially in the Anthropocene where habitat loss and fragmentation are expected to continue (Defries et al, 2010; Hansen et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
“…Our results are consistent with other studies that examined how pollinator functional traits (body morphology, body size, foraging strategy) influence pollination success. In other systems, high morphological affinity between floral structures and pollinator characteristics have been reported to facilitate flower handling (Maglianesi et al, 2014), increase pollen removal (Watts et al, 2012; Rhodes et al, 2017; Temeles et al, 2019), and enhance the genetic diversity of sired seeds (Valverde et al, 2019). In H. tortuosa , flower morphology is closely matched by the long and curved bills of traplining hummingbirds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our estimates of effective pollen movements likely reflect true pollen transport distances, regardless of compatibility. In other forb species, pollen transport distances are much shorter than 16 m (Evans et al., ; Thavornkanlapachai et al., ; Valverde et al., ), with pollen sometimes moving <1 m between mates (Evans et al., , Valverde et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, visit frequency or total body size cannot totally explain pollen load size, since larger pollinator species often make brief visits, decreasing the probability of pollen collection; thus, in such cases, other features could be more relevant to the amount of pollen extracted. For example, a study of Eurysimum mediohispanicum populations [ 10 ] found that large bees make short visits, but they handle the flower very quickly and with great accuracy, thereby increasing their total pollen load. In this sense, the pollinators’ handling abilities could be a key factor in improving the amount of pollen extracted per visit, since staying longer can increase the probability of them extracting more grains per visit [ 11 ].…”
Section: Introductionmentioning
confidence: 99%